Daon
OK I see that
\(\displaystyle \displaystyle 38 = (5 - 1) * 9 + 2 \rightarrow (5,\ 2) \rightarrow 22,222 = 2 * \sum_{i=0}^410^i \rightarrow (4,\ 2) = 4 * 9 + 2 = 38.\)
That is very elegant. But that still implies a single rule and its inverse (although it can be expressed in a number of ways). Is it possible to demonstrate that the rule is or is not unique?
I think I may not understand your question, but I will try to explain myself better while hopefully touching on your question. There are an infinite number of bijections, but as problem solvers we opt for the most intuitive ones. Most of the bijections will not be formulaic, but here are two of them, showing non-uniqueness of the map:
We shall consider \(\displaystyle n=9q_n+r_n\) where \(\displaystyle q_n,r_n\) are the unique positive integers corresponding to \(\displaystyle n\) given by the modified division algorithm: \(\displaystyle r_n\in\{1,...,9\}\) (so \(\displaystyle q_9=0\) but \(\displaystyle q_{10}=1\)).
\(\displaystyle f_1, f_2:\mathbb{N}\to \{1,2,...,9\}\times \mathbb{N}\) where
\(\displaystyle f_1(n) = f_1(9q_n+r_n) = \left(r_n \, , q_n+1\right)\)
\(\displaystyle f_2(n) = f_2(9q_n+r_n) = \begin{cases} \left(r_n+1 \, , q_n+1\right) & r_n\neq 9\\ \left(1 \, , q_n+1\right) & r_n=9\end{cases}\)
For example, let's look at \(\displaystyle f_1\).
\(\displaystyle f_1(1) = (1,1)\,\,\) since \(\displaystyle 1 = 9\cdot \underbrace{0}_{q_1}+\underbrace{1}_{r_1}\)
\(\displaystyle f_1(2) = (2,1)\,\,\) since \(\displaystyle 2 = 9\cdot \underbrace{0}_{q_2}+\underbrace{2}_{r_2}\)
\(\displaystyle f_1(3) = (3,1)\,\,\) since \(\displaystyle 3 = 9\cdot \underbrace{0}_{q_3}+\underbrace{3}_{r_3}\)
....
\(\displaystyle f_1(9) = (9,1)\,\,\) since \(\displaystyle 9 = 9\cdot \underbrace{0}_{q_9}+\underbrace{9}_{r_9}\)
\(\displaystyle f_1(10) = (1,2)\,\,\) since \(\displaystyle 10 = 9\cdot \underbrace{1}_{q_{10}}+\underbrace{1}_{r_{10}}\)
etc. By contrast for \(\displaystyle f_2\) we have
\(\displaystyle f_2(1) = (2,1)\)
\(\displaystyle f_2(2) = (3,1)\)
\(\displaystyle f_2(3) = (4,1)\)
\(\displaystyle f_2(9) = (1,1)\)
\(\displaystyle f_2(10) = (2,2)\), etc.
Essentially I cyclically permuted the first ordinate of each pair, you can similarly define 9! different bijections just by considering the ways you may permute the rows of this 9-row by infinite column matrix.
Then for the function \(\displaystyle g:\{1,...,9\}\times \mathbb{N}\to Y\) given by \(\displaystyle g(a,n) = \underbrace{aaa...a}_{n\,\, times}\), both functions: \(\displaystyle F_1=g\circ f_1\) and \(\displaystyle F_2=g\circ f_2\) we get different bijections from \(\displaystyle \mathbb{N}\) to \(\displaystyle Y\)